Engineering of ovarian tissue for ovarian dysfunctions: A review - Aliya Zhylkybekova; Gulbakit K. Koshmaganbetova; Myltykbay S. Rysmakhanov; Nurgul Abdullayevna Abenova; Nadiar Maratovich Mussin; Asset Askerovich Kaliyev; Mahdi Mahdipour; Amin Tamadon (Asian Pacific Journal of Reproduction)
This review explores tissue engineering as a potential solution for reproductive health issues in women caused by genetic or acquired diseases, such as premature ovarian failure or oophorectomy. The loss of ovarian function can lead to infertility, osteoporosis, and cardiovascular disease. Hormone replacement therapy is a common treatment, but it has limitations and risks. The review focuses on two main approaches in tissue engineering: scaffold-based (3D printing, electrospinning, decellularization) and scaffold-free (stem cell transplantation, organoid cultivation). Both approaches show promise in preclinical studies for creating functional ovarian tissue. Challenges include vascularization, innervation, long-term function, and safety. Despite these challenges, tissue engineering offers a potential avenue for restoring fertility and hormone balance in women with ovarian dysfunction.